2020
DOI: 10.1186/s13014-020-01702-4
|View full text |Cite
|
Sign up to set email alerts
|

The decreased mean platelet volume is associated with poor prognosis in patients with oropharyngeal cancer treated with radiotherapy

Abstract: Background There is considerable evidence that platelets contribute to cancer growth and metastatic dissemination. In recent studies, altered mean platelet volume (MPV) has been associated with prognosis in different types of cancer. However, the prognostic role of the MPV in head and neck squamous cell cancer (HNSCC) is currently discussed controversially. The present study was performed to analyze and further elucidate the prognostic significance of the MPV in HNSCC. Methods A total of 319 oropharyngeal sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Recent studies showed that RDW was significantly higher in DTC and PTC patients than in the control group (16,29). In another study, when the postoperative results of patients who underwent thyroidectomy due to atypia/follicular lesion of undetermined significance were divided as benign and malignant, preoperative RDW was found to be higher in the malignant group than in the benign group (30). In our study, higher RDW was found in all groups compared to the control group.…”
Section: Discussionsupporting
confidence: 51%
“…Recent studies showed that RDW was significantly higher in DTC and PTC patients than in the control group (16,29). In another study, when the postoperative results of patients who underwent thyroidectomy due to atypia/follicular lesion of undetermined significance were divided as benign and malignant, preoperative RDW was found to be higher in the malignant group than in the benign group (30). In our study, higher RDW was found in all groups compared to the control group.…”
Section: Discussionsupporting
confidence: 51%
“…32 Moreover, platelets can get activated on encountering circulating tumor cells which result in the formation of microparticles that can potentially promote the invasiveness of tumor cells. 33 Therefore, this close interplay between high MPV and poor prognosis of cancers can be a reasonable hypothesis. In contrast, our ndings do not support the hypothesis that an MPV level is a prognostic factor for poor outcomes in lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…32 Moreover, platelets can be activated upon encountering circulating tumor cells, which results in the formation of microparticles that can potentially promote the invasiveness of tumor cells. 33 Therefore, this close interplay between high MPV and poor prognosis in cancer is a reasonable hypothesis. By contrast, our findings do not support the hypothesis that MPV is a prognostic factor for poor outcomes in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%